Human pulpal responses to peroxides - Soares, Diana Gabriela [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2016)
It is known that most patients subjected to professional tooth bleaching report posttreatment hypersensitivity that varies from slight to intolerable. The pathway for tooth bleaching-induced sensitivity has been correlated with the capability of hydrogen peroxide (H2O2), the main active component of bleaching gels, to diffuse through enamel and dentin to reach the pulp tissue. Since H2O2is a toxic reactive oxygen species with a high oxidative power, it is expected that the contact of this molecule with the pulp tissue promotes oxidative cells damage leading to local connective infl ammation that trigger nociceptive stimulus. However, as this clinical symptom is transient, discussion about how relevant is this adverse collateral effect to the pulp-dentin complex remains. Then, in this chapter, the authors describe some relevant clinical and laboratorial data currently provided by a number of in vitro and in vivo studies in which traditional in-offi ce (professional) and at-home bleaching therapies were tested, as well as discuss alternative tooth bleaching protocols that may prevent or at least minimize the negative effects of these esthetic treatments to the pulp tissue vitality.